Systematic analysis on peer-to-peer botnet attack detection - Binte istiaq, Faiza; E Mohammad, Rubaiyat; Tasnia, Moriom; Hassan, Kazi Moinul; Tabassum, Tanjim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.